2017
DOI: 10.3389/fgene.2017.00133
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Gene Expression Effects of Disease-Associated Variants: A Lesson from SNCA rs356168

Abstract: The SNCA intronic single nucleotide polymorphism (SNP), rs356168, has been associated with Parkinson’s disease (PD) in large genome wide association studies (GWAS). Recently, the PD-risk allele, rs356168-G was shown to increase SNCA-mRNA expression using genome edited human induced pluripotent stem cells (iPSC)-derived neurons. In this study, as means of validation, we tested the effect of rs356168 on total SNCA-mRNA levels using brain tissues, temporal and frontal cortex, from healthy control donors. Carriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…2 SNCA GWAS hits have been investigated as potential brain eQTLs in a number of previous studies without convincing results, including the large Genotype Tissue Expression 34 and BRAINEAC 40 databases, as well as a recent negative follow-up study of the proposed functional variant rs356168. 41 This suggests that regulation is complex, and refined analyses may be needed to detect disease-relevant mechanisms. Previous studies have investigated SNCA splice variants affecting coding exons, 42 but variation in 5′UTR expression has to our knowledge not been studied in relation to PD susceptibility and risk SNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 SNCA GWAS hits have been investigated as potential brain eQTLs in a number of previous studies without convincing results, including the large Genotype Tissue Expression 34 and BRAINEAC 40 databases, as well as a recent negative follow-up study of the proposed functional variant rs356168. 41 This suggests that regulation is complex, and refined analyses may be needed to detect disease-relevant mechanisms. Previous studies have investigated SNCA splice variants affecting coding exons, 42 but variation in 5′UTR expression has to our knowledge not been studied in relation to PD susceptibility and risk SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Such an eQTL effect is particularly plausible in the case of SNCA , where the dose‐dependent pathogenic effect of increased expression has been demonstrated in monogenic PD caused by genomic multiplications . SNCA GWAS hits have been investigated as potential brain eQTLs in a number of previous studies without convincing results, including the large Genotype Tissue Expression and BRAINEAC databases, as well as a recent negative follow‐up study of the proposed functional variant rs356168 . This suggests that regulation is complex, and refined analyses may be needed to detect disease‐relevant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The same SNP was subsequently tested for changes in SNCA expression in frontal and temporal cortex of a cohort of 134 healthy individuals. That study concluded the opposite effect for the G-allele with an ~20% decrease in alpha-synuclein mRNA in individuals homozygous for the G-allele (Glenn et al, 2017 ).…”
Section: Gwas Hits In the Snca Gene Increase Pd Rimentioning
confidence: 99%
“…Out of 25 PD-associated SNPs, seven have been reported to influence alpha-synuclein levels, however, some findings are controversial (Supplemental Table 2 ). Six SNPs within intron 4 and 3′ region were studied for total alpha-synuclein mRNA levels in post-mortem brain samples, blood, or in vitro with variable findings for alpha-synuclein expression (Fuchs et al, 2007a , 2008 ; Westerlund et al, 2008 ; Sotiriou et al, 2009 ; Mata et al, 2010 ; Hu et al, 2012 ; Rhinn et al, 2012 ; Cardo et al, 2014 ; Glenn et al, 2017 ).…”
Section: Gwas Hits In the Snca Gene Increase Pd Rimentioning
confidence: 99%
“…Measurement of total SNCA mRNA levels showed a significant increase in the presence of the risk allele, which was complemented by eQTL analysis of SNCA mRNA in the brain of patients with PD and control subjects, conferring risk for PD [96]. An opposite effect of rs356168 on SNCA mRNA levels was reported in the brains of healthy individuals [97]. The contradicting results might be due to technical limitations or methodological differences.…”
Section: Intronic Variationmentioning
confidence: 95%